Why do firms switch their main bank? Theory and evidence from Ukraine - Andreas Stephan; Andriy Tsapin; Oleksandr Talavera (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We examine why firms change their main bank and how this affects loans, interest payments and firm performance after switching. Using unique firm-bank matched Ukrainian data, the treatment effect estimates suggest that more transparent and riskier companies are more likely to switch their main bank. Importantly, main bank power, measured by equity holdings, appears to be one of the main drivers of firm switching behavior. Furthermore, we find that firms have lower performance after changing their main bank as they have to contend with higher interest payments. - Financial constraints ; switching ; main bank power ; firm performance ; Ukraine
Keywords: G21; G30; G32; 330; Unternehmen; Hausbank; Lieferanten-Kunden-Beziehung; Wechselkosten; Unternehmensentwicklung; Verschuldungsrestriktion; Ukraine